(untitled) (El Hilo de la Fabula, 2015)
This article exposes the journey through a process of research and documentation of the project Migraciones internas, about the Spanish pieds noirs; it was guided by the playwright of the final drama Los desterrados, hijos de Eva. Here you will find some of its motivations and the plot used to give the voice to the ones the History has forgotten, as well as its reception in a performance, in the context of the Arab Spring.